Extraction of anthraquinone glycosides from the mixture of cassia alata stems and leaves - Mohamad Roslan, Dzulkifli (2013)
The main objective of this research is to separate anthraquinone glycosides from the mixture of cassia alata stems and leaves. Besides it is also to find the kinetic of anthraquinone glycosides separation from the mixture of cassia alata stems and leaves using ultrasound extraction method. The mixtures of Cassia alata stems and leaves were dried in open shade. Dried Cassia alata will be milled to 60 mesh powder using mortar. The mixtures of Cassia alata stems and leaves powder will be stored at ambient temperature. The mixture of Cassia alata stems and leave powder (500 mg) was dissolved with 50 ml of different solvent-water ratio (20:80, 40:60, 60:40, 80:20 and 100:0, v/v) in an ultrasonicator bath. Time was used for sonication are 10, 20, 30, 40 and 50 minutes using ultrasonic cleaning bath (JAC ultrasonic type 1505) which nominal power is 250 W dimension 300x1 50x1 50 mm), frequency of 40 kHz and volume of 5.7 L. The extraction process was conducted at five different temperatures which is 20, 30, 40, 50 and 60 °C. The sample was allowed to cool at room temperature.Then at vacuum filter, dry the filter disk in the oven at 103°C to 105°C for 1 hour, cool in a desiccator and weigh. After that, rotary evaporator was used to record distillate temperature and measure the volume of collected product from receiving vessel. Combined all the collected distillate in a container and at the end of the experiment, measure its overall volume and composition. The volume and composition of the concentrate was determined. High Performance Chromatography (HPLC) was used to analyze the samples. A sample was injected into the Eurospher 100-5 NH2 column. The samples was evaluated at a flow rate of 1 mL/min using a solvent system of acetonjtrile:water (80:20, v/v). From the result we can conclude that the mixture of cassia alata leaves and stems has been successfully extract the anthraquinone glycosides. The extraction process has been affected by the variation of parameter such as by extraction time, extraction temperature, extraction power and ratio of solvent to water. The optimum yield can be extract from the mixture of cassia alata stem and leaves was found by the extraction time of 30 mm, extraction temperature of 40 °C and ratio of solvent to water of 80:20 (v/v).